2017
DOI: 10.1039/c7gc01583f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3-alkoxypropan-1,2-diols from glycidol: experimental and theoretical studies for the optimization of the synthesis of glycerol derived solvents

Abstract: Optimized green synthesis of glyceryl monoethers from alcohols and glycidol through experimental and computational studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 61 publications
3
45
0
Order By: Relevance
“…[8][9][10][11] Among oxiranes,g lycidol (GLY) has attracted much attention, not only because it can act as cornerstone for the synthesis of more complexm olecules, but also because the presence of ah ydroxy group profoundly influences its reactivity. [24,25] Nevertheless, such as ynthesis was recently accomplished both under basic conditions [26] and in the presence of acidic heterogeneous (i.e.,A mberlyst IRA-400a nd Nafion NR50) [27,28] and homogenous( metal triflates) [29,30] catalytic systems. [12,13] Among the possible products that can be obtained by nucleophilic ring-opening of GLY, monoalkyl glyceryl ethers (MAGEs) are ar elevant class of molecules, not only because they represent one of the most successful examples of glycerol valorizationb ut also because they find application in many significant industrial areas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] Among oxiranes,g lycidol (GLY) has attracted much attention, not only because it can act as cornerstone for the synthesis of more complexm olecules, but also because the presence of ah ydroxy group profoundly influences its reactivity. [24,25] Nevertheless, such as ynthesis was recently accomplished both under basic conditions [26] and in the presence of acidic heterogeneous (i.e.,A mberlyst IRA-400a nd Nafion NR50) [27,28] and homogenous( metal triflates) [29,30] catalytic systems. [12,13] Among the possible products that can be obtained by nucleophilic ring-opening of GLY, monoalkyl glyceryl ethers (MAGEs) are ar elevant class of molecules, not only because they represent one of the most successful examples of glycerol valorizationb ut also because they find application in many significant industrial areas.…”
mentioning
confidence: 99%
“…[12,13] Among the possible products that can be obtained by nucleophilic ring-opening of GLY, monoalkyl glyceryl ethers (MAGEs) are ar elevant class of molecules, not only because they represent one of the most successful examples of glycerol valorizationb ut also because they find application in many significant industrial areas. [24,25] Nevertheless, such as ynthesis was recently accomplished both under basic conditions [26] and in the presence of acidic heterogeneous (i.e.,A mberlyst IRA-400a nd Nafion NR50) [27,28] and homogenous( metal triflates) [29,30] catalytic systems. [24,25] Nevertheless, such as ynthesis was recently accomplished both under basic conditions [26] and in the presence of acidic heterogeneous (i.e.,A mberlyst IRA-400a nd Nafion NR50) [27,28] and homogenous( metal triflates) [29,30] catalytic systems.…”
mentioning
confidence: 99%
“…MAGEsh ave been also synthesized by glycerol etherification with n-butanol( 150 8C, 6.5 mol %B i(OTf) 3 as catalyst, 24 h) and 1-dodecanol (130 8C, 1equivcetyltrimethylammonium bromide (CTAB) and 10 wt %o fH + as catalysts,2 4h)i nt he presence of homogeneous catalysts with good yields (70 %a nd 60 %r espectively). [11] Only af ew studies have reported the preparation of MAGEs startingf rom glycidol [8,[14][15][16] and, in this context,M AGEs have been obtained with high selectivity by using homogeneous catalysts and very preliminary results have been reported in the presence of heterogeneous basic catalysts (71 %w /w toward glycidol with Amberlyst IRA-400). [8,35] Generally,t his approachp ermitsM AGEst ob eo btained with high selectivity,f avoring the developmento fs olvents,i nm ostc ases with av ery low eco-toxicity [36] and with tunable properties.…”
Section: Background: Synthetic Approaches For Mages Preparationmentioning
confidence: 99%
“…[33,34] Industrial building blocks, alternative to glycerol, have been successfully used to prepareM AGEs, such as glycidol, epichlorohydrin, allyl alcohol, and 3-chloro-1,2-propanediol. [16] In our previousstudies, [14,15] we reported the selectivepreparation of MAGEs under mild reactionc onditions (80 8C, 0.01 mol %c atalyst, alcohol/glycidol 9:1m olarr atio, 1h), by Scheme1.Investigated routes for the synthesis of glycidol. [11] Only af ew studies have reported the preparation of MAGEs startingf rom glycidol [8,[14][15][16] and, in this context,M AGEs have been obtained with high selectivity by using homogeneous catalysts and very preliminary results have been reported in the presence of heterogeneous basic catalysts (71 %w /w toward glycidol with Amberlyst IRA-400).…”
Section: Background: Synthetic Approaches For Mages Preparationmentioning
confidence: 99%
See 1 more Smart Citation